The Effect of The Addition Lactace Enzyme in Goats Milk on The Manufacture of Yogurt Was Review from pH, Moisture Content, Viscosity, and Total Dissolved Solids - Susilo, Agus; Wicaksono, Irfan Resi (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
The purpose of this study was to determine the effect of adding lactase enzymes to goat milk in yogurt production, specifically in terms of pH, moisture content, viscosity, and total dissolved solids. The research material used was goat milk with the addition of lactase enzymes to hydrolyze sugars into simpler forms. The study was conducted with five treatments and four replications. The treatments involved adding powdered lactase enzymes at concentrations of 0.00%, 0.25%, 0.50%, 0.75%, and 1.00% to goat milk yogurt. The variables measured were pH, moisture content, viscosity, and total dissolved solids. Data were analyzed using analysis of variance (ANOVA), followed by Duncan's Multiple Range Test (DMR) for further comparison. The results of the study showed that the addition of lactase enzyme had a very real effect (P<0.01) on moisture content, viscosity, and total dissolved solids. The average water content score was 81.84-74.63%. The average viscosity score value was 32.67-40.33 cps. And the average total score value of dissolved solids is 3196-2997 ppm.  The addition of lactase enzyme of 1.00% produced the best yogurt reviewed from the pH value at P4 (4.25), moisture content at P4 (74.63%), viscosity at P4 (40.33 cps), and total dissolved solids at P4 (2997 ppm).